Assessing the Mathematical Reasoning Required in Geometry Examination Tasks for the Filipino Deaf/Hard-of-Hearing Learners - De Jesus, Vitus Paul L. (Archīum Ateneo, 2024)
The study examined the quality of mathematical reasoning required for the Geometry examination tasks that were given to Deaf and Hard-of-Hearing (D/HH) mainstream classroom learners of an educational institution. As a prevailing practice in the crafting of examinations for basic education mathematics in the Philippines, the school also used the revised Bloom's taxonomy as the primary basis. With the use of such framework, however, there seems to be a disagreement arising between the teacher's classification of the items and the cognitive demand that the items actually project for the learners. Lithner's (2005) framework seems to address this issue as it takes into account the possible similarities of learning material examples/exercises and the actual examination items. This study has two objectives: (1) determine to what extent is it possible to solve Geometry examination tasks given to the D/HH mainstream classroom learners, and (2) identify the relationship that seems to emerge between the cognitive domain categories of the revised Bloom's taxonomy and the types of mathematical reasoning of Lithner's framework. The study aims to contribute to a seemingly scarce local literature and help improve D/HH education in the Philippines, particularly on the assessment aspect.